Correlation between FINA points and isokinetic torque symmetry index of the shoulder joint in swimmers - Carneiro, N. B.; dos Santos, Y. S.; Castro, F. A. d. S.; Franken, M.; de Jesus, K.; de Jesus, K. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The front crawl technique is considered the fastest and most frequently used technique in swimming training (Tourny-Chollet, Seifert, & Chollet, 2009) being characterized by upper limb cycles with propulsive and non-propulsive phases (Chollet, Chalies, & Chatard, 2000). However, despite the cyclical nature of this swimming technique, the symmetry of propulsive forces cannot be affirmed (Formosa, Sayers, & Burkett, 2013). One of the causes of asymmetry that affects propulsion are the differences in bilateral forces that cause three effects: 1) on the rotational balance of the body, causing misalignment; 2) the smaller contribution of the weaker side in the production of propulsive forces; and 3) fatigue due to the attempt to maintain swimming speed causing the stronger side to apply greater force to compensate for the weaker side (Sanders, 2013). It has been reported that the application of symmetrical force between the right and left sides of the body is a factor that influences swimming performance by improving body alignment, reducing active drag, and decreasing intra-cycle velocity variations (Sanders, Thow, & Fairweather, 2011). However, swimmers can develop bilateral force asymmetries as a result of various factors (e.g., injuries, technique development, preferred breathing side, among others), reducing their ability to produce propulsive forces (Sanders et al., 2011). Investigating performance factors, such as the symmetr index, is critical to understanding bilateral strength in swimmers. Therefore, the aim was to analyze the relationship between FINA points classification and the symmetry index (SI) of isokinetic torque in internal rotation (IR), external rotation (ER), flexion (FL), and extension (EX) movements of the shoulders in swimmers, hypothesizing that FINA points influences isokinetic torque symmetry.